A recyclable biochar bead adsorbent and its preparation method and application
By mixing the egg shell and peanut shell biomass powder in a specific proportion and calcining under specific conditions, a structure-stable biochar bead adsorbent is prepared, which solves the structural instability of the biochar adsorbent in the prior art. The structure of the biochar adsorbent is unstable and the adsorption efficiency is low in the prior art. Problem, efficient phosphorus removal and recyclability are achieved.
Patent Information
- Application Number
- CN202310267803.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-16
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-03-16
AI Technical Summary
The existing biochar adsorbents are unstable during the phosphate adsorption process, difficult to recover, and have low adsorption efficiency.
The structure is prepared by mixing the eggshell biomass powder and the peanut shell biomass powder in a specific proportion, adding sodium alginate, heating and dissolving, and then cooling naturally, dropping into the aqueous CaCl2 solution to harden into balls, and calcining under specific calcining conditions. Stable biochar bead adsorbent.
The biochar beads maintain the spherical structure during the phosphate adsorption process, ensure their recyclability, and significantly improve the phosphorus removal rate.
Smart Images

Figure CN116099504B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid waste resource utilization and water treatment materials, and in particular to a recyclable biochar bead adsorbent and a preparation method and application thereof. Background Art
[0002] Generally speaking, phosphorus is the limiting nutrient for eutrophication in freshwater bodies, so controlling the phosphorus content in freshwater bodies is crucial to preventing and controlling eutrophication.
[0003] Huge amounts of agricultural waste are generated every year, and common treatment methods include incineration and landfill. Incineration is expensive and produces a large amount of greenhouse gases; landfilling of agricultural waste also produces leachate that pollutes groundwater and generates methane, which is more climate-damaging than CO2.
[0004] Although biochar prepared from common agricultural waste has a certain adsorption capacity, its surface electronegativity leads to a very low adsorption efficiency for anions such as phosphate. In order to improve the adsorption capacity of such biochar anions, a modification method of loading metal ions on biochar is usually adopted. Eggshells contain up to 94%wt of CaCO3, which is a green and natural source of calcium metal modifiers. In addition, peanut shells contain lignin (36.1%), cellulose (44.8%) and hemicellulose (5.6%), and have sufficient surface area and porosity, which are suitable for use as a porous matrix to produce biochar. Eggshell-modified peanut shell biochar powder can reach a phosphate adsorption capacity of more than 300mg / g.
[0005] It is worth noting that common biochar adsorbents often turn into powder and disperse in the solution during the adsorption process, making them difficult to recycle. The biochar beads prepared by the sodium alginate cross-linking method are expected to achieve the preparation of biochar beads with stable structure, which is beneficial to maintaining soil fertility and moisture and slowing down the loss of nitrogen and phosphorus in the soil. However, even if the biochar beads are prepared by the sodium alginate cross-linking method, they cannot be made into biochar beads that are durable and structurally stable without finding the right preparation conditions and steps; even if they are made into biochar beads that are durable and structurally stable, they may not be able to maintain a spherical shape during the adsorption process for easy recycling.
[0006] Therefore, there is an urgent need to explore a method for preparing a biochar bead adsorbent with high adsorption and phosphorus removal performance and a stable structure before and after adsorption using agricultural waste. Summary of the invention
[0007] The present invention provides a recyclable biochar bead adsorbent and a preparation method and application thereof. The biochar bead adsorbent can not only ensure that the spherical structure is always maintained during the phosphate adsorption process, thereby achieving the recyclability of the biochar beads, but also has a high phosphorus removal rate.
[0008] The specific technical solutions are as follows:
[0009] A method for preparing a recyclable biochar bead adsorbent comprises the following steps:
[0010] (1) mixing egg shell biomass powder and peanut shell biomass powder in water according to a certain proportion, adding sodium alginate, heating to dissolve, and naturally cooling to room temperature to obtain a precursor slurry;
[0011] The mass ratio of the egg shell biomass powder to the peanut shell biomass powder is 1:1-3; the particle size of the egg shell biomass powder is 0.15-0.18 mm; the particle size of the peanut shell biomass powder is 0.15-0.25 mm;
[0012] (2) The precursor slurry of step (1) is dropped into a CaCl2 aqueous solution to harden into balls. The hardened hydrogel balls are dried to constant weight and then calcined at 700°C to 775°C for 1 to 2 hours in a nitrogen atmosphere to obtain a biochar bead adsorbent.
[0013] Furthermore, in step (1), the mass percentage of the egg shell biomass powder and the peanut shell biomass powder in water is 4 to 6%wt.
[0014] Furthermore, in step (1), the mass percentage of sodium alginate in the precursor slurry is 1.5-3%wt.
[0015] Furthermore, in step (1), the temperature for heating and dissolving is 55 to 65° C., and the stirring time is 20 to 35 min.
[0016] Furthermore, in step (2), after the precursor slurry is dripped into the CaCl2 aqueous solution, the mass percentage of CaCl2 is 3wt% to 7wt%, and the hardening time is 16 to 20h.
[0017] Furthermore, in step (2), the hardened hydrogel spheres are first washed with deionized water and CaCl2, and then dried to constant weight.
[0018] Furthermore, in step (2), the heating rate during the calcination process is 4 to 5°C / min.
[0019] Furthermore, in step (1), the mass ratio of egg shell biomass powder to peanut shell biomass powder is 1:3; the particle size of the egg shell biomass powder is 0.15 mm; the particle size of the peanut shell biomass powder is 0.15-0.25 mm; the calcination temperature is 750-775°C, and the calcination time is 1.5 h.
[0020] The present invention also provides the use of the biochar bead adsorbent as described above in adsorbing phosphate in water.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention mixes eggshell biomass powder and peanut shell biomass powder of specific dosage ratio and specific particle size, hardens them into balls, and calcines them under specific calcination conditions. The obtained biochar bead adsorbent can not only ensure that the spherical structure is always maintained during the phosphate adsorption process, realize the recyclability of the biochar beads, but also has a high phosphorus removal rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is the SEM image of biochar adsorbent;
[0024] Among them, a) and b) are E; c) and d) are EC1:1; e) and f) are C; f) and g) are EC1:3-750(b); h) and i) are EC1:1-775(b).
[0025] Figure 2 is the SEM image of the biochar adsorbent after adsorption;
[0026] Among them, a) and b) are E; c) and d) are EC1:1; e) and f) are C; g) and h) are 750-1:3 (b); i) and j) are 775-1:1 (b).
[0027] Figure 3 FTIR spectra before and after adsorption;
[0028] Among them, a) is E, EC1:1, PS biochar; b) is 750-1:3 (b) and 775-1:1 (b).
[0029] Figure 4 is the XRD pattern before and after adsorption;
[0030] Among them, a) is E; b) is EC1:1; c) is C; d) is 750-1:3 (b); e) is 775-1:1 (b). DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with specific embodiments. The following are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto.
[0032] The characterization analysis methods in the following examples are as follows:
[0033] (1) Field emission scanning electron microscopy and X-ray spectrometer characterization: The microscopic morphology and structure of the biochar bead surface were analyzed by field emission scanning electron microscopy (SEM), and the acceleration voltage of the SEM used was 5 kV. At the same time, the elemental composition and percentage content of the biochar bead surface were analyzed by an X-ray energy dispersive spectrometer (EDS) equipped with the SEM.
[0034] (2) Surface, pore volume and pore size analysis
[0035] The N2 adsorption-desorption isotherms of the biochar beads were measured by surface analyzer (BET) at 77.35 K, and the specific surface area (S BET ), pore volume (TPV) and average pore size.
[0036] (3) X-ray crystal diffractometer characterization
[0037] The crystal structure of the biochar beads was analyzed by X-ray diffractometer (XRD). The XRD used Cu Kα as the X-ray source and scanned in the range of 5-80° with a scanning step of 0.02° and a scanning speed of 0.1s.
[0038] (4) Fourier transform infrared spectroscopy characteristics
[0039] The biochar beads were dried, and then ground and mixed with dried potassium bromide (spectral grade) at a mass ratio of 1:100, and passed through a 1 mm sieve. The prepared materials were then pressed into thin sheets, and the characteristic chemical bonds and functional groups of the biochar beads were analyzed using Fourier transform infrared spectroscopy (FTIR), with the FTIR wave number scanning range of 400-4000 cm -1 .
[0040] Among them, XRD data were fitted and analyzed using jade 6, and FTIR data and other adsorption experimental data were fitted and analyzed using Excel and Origin 2021. In addition, Excel was used to draw tables and Origin 2021 was used to draw graphs.
[0041] Example 1
[0042] A recyclable biochar bead adsorbent (sequence 18 in Table 4), the specific preparation method thereof is as follows:
[0043] (1) After the egg shell biomass powder passed through a 100-mesh sieve and the peanut shell biomass powder passed through a 100-mesh sieve are uniformly mixed in water at a mass ratio of 1:3, 5%wt of the mixture is added, and 2%wt of sodium alginate is added, and the mixture is heated to 60°C and stirred for 30 minutes, and the slurry is naturally cooled to room temperature to obtain a precursor slurry;
[0044] (2) The mixed slurry of step (1) is dropped into a slowly stirred 5wt% CaCl2 solution to form a ball and harden it into a ball for 18 hours. The hardened hydrogel ball is then dried in a constant temperature oven at 105°C to constant weight. The dried hydrogel is then calcined in a tubular furnace at 750°C (heating rate 5°C / min) with a nitrogen flow rate of 0.025L / min for 1.5 hours. Finally, the finished biochar beads (abbreviated as EC 1:3-750(b)) are obtained, which can basically maintain a spherical shape after absorbing phosphorus.
[0045] Example 2
[0046] A recyclable biochar bead adsorbent (sequence 15 in Table 4), the specific preparation method thereof is as follows:
[0047] (1) After the egg shell biomass powder passed through a 100-mesh sieve and the peanut shell biomass powder passed through a 60-mesh sieve are uniformly mixed in water at a mass ratio of 1:1 at a weight ratio of 5% wt, 2% wt of sodium alginate is added, and the mixture is heated to 60° C. and stirred for 15 minutes. The slurry is naturally cooled to room temperature to obtain a precursor slurry.
[0048] (2) The mixed slurry was dripped into a slowly stirred 5wt% CaCl2 solution to form a ball and hardened into a ball for 24 hours. After hardening, it was washed with deionized water, and then the hardened hydrogel ball was dried in a 60℃ constant temperature oven to constant weight, and then the dried hydrogel was calcined in a tube furnace at a nitrogen flow rate of 0.015L / min and 775℃ (heating rate 5℃ / min) for 1.5h. Finally, the finished biochar beads (abbreviated as: EC 1:1-775(b)) were obtained, which can partially maintain the spherical shape after absorbing phosphorus.
[0049] Example 3
[0050] A recyclable biochar bead adsorbent (sequence 20 in Table 4), the specific preparation method thereof is as follows:
[0051] (1) After the egg shell biomass powder passed through a 100-mesh sieve and the peanut shell biomass powder passed through a 100-mesh sieve are uniformly mixed in water at a mass ratio of 1:1 at a rate of 5%wt, 2%wt sodium alginate is added, and the mixture is heated to 60°C and stirred for 30 minutes. The slurry is naturally cooled to room temperature to obtain a precursor slurry.
[0052] (2) The mixed slurry is dropped into a slowly stirred 5wt% CaCl2 solution to form balls and harden for 18 hours. The hardened hydrogel balls are then dried in a constant temperature oven at 105°C to constant weight. The dried hydrogel is then calcined in a tubular furnace at 750°C (heating rate 5°C / min) with a nitrogen flow rate of 0.025L / min for 1.5 hours. Finally, the finished biochar beads (abbreviated as EC 1:1-750) are obtained, which can mostly maintain a spherical shape after absorbing phosphorus.
[0053] Comparative Example 1
[0054] The preparation method of eggshell biochar powder (E) is as follows: the eggshell is washed with pure water for several times and then dried, then ground with a grinder, and finally sieved with a 100-mesh sieve. The sieved eggshell powder sample is placed in a programmable tubular electric furnace, and the material powder is heated to 800°C at a rate of 5°C / min under a N2 atmosphere and maintained for 2 hours. After the furnace is cooled to room temperature, the finished eggshell biochar powder is obtained.
[0055] Comparative Example 2
[0056] The preparation method of peanut shell biochar powder (C) is as follows: washing the peanut shell with pure water for several times and then drying it, then grinding it with a grinder, and finally passing it through a 100-mesh sieve. The sieved peanut shell powder sample is placed in a programmable tubular electric furnace, and the material powder is heated to 800°C at a rate of 5°C / min under a N2 atmosphere and maintained for 2 hours. After the furnace is cooled to room temperature, the finished peanut shell biochar powder is obtained.
[0057] Comparative Example 3
[0058] The preparation method of the biochar powder (EC 1:1) mixed with egg shell and peanut shell in a mass ratio of 1:1 is as follows: the egg shell and peanut shell are washed with pure water for several times in a mass ratio of 1:1 and then dried, then ground with a grinder, and finally passed through a 100 mesh sieve. The sieved mixed powder sample is placed in a programmable tubular electric furnace, and the material powder is heated to 800°C at a rate of 5°C / min under a N2 atmosphere and maintained for 2 hours. After the furnace is cooled to room temperature, a finished product of the egg shell and peanut shell mixed biochar powder with a mass ratio of 1:1 is obtained.
[0059] EC 1:3-750(b) prepared in Example 1, EC 1:1-775(b) prepared in Example 2, adsorbent E prepared in Comparative Example 1, adsorbent C prepared in Comparative Example 2, and EC 1:1 prepared in Comparative Example 3 were characterized and analyzed, and the results were as follows:
[0060] 1. Surface morphology, elemental composition and BET analysis of biochar before and after adsorption
[0061] like Figure 1As shown in the figure, eggshell biochar and peanut shell biochar before adsorption showed different microscopic morphologies. Eggshell biochar E showed obvious nanoparticle structure and agglomeration phenomenon; while the surface of peanut shell biochar C showed a flat and microporous fiber structure and a trace amount of CaCO3 crystal structure, showing blocky calcite crystal form and needle-shaped aragonite crystal form. Eggshell nanoparticles can still be observed on the surface of biochar EC1∶1, but the number of particles is less than that of E, and its particles are covered on the peanut shell fiber structure. It is speculated that the substances on the surface of E and EC1∶1 may mainly be vaterite crystal form CaCO3 and Ca(OH)2. Due to the hydrogelation with sodium alginate and the cross-linking process of calcium chloride in the preparation process of the beaded adsorbent, its surface microscopic morphology is more complex, and a large number of agglomerates can be observed to be tightly combined.
[0062] Figure 2 The SEM image after adsorption is shown. After the reaction, fine flocculent particles and amorphous particles appeared in E and EC1:1 adsorbents. Combined with the subsequent XRD and FTIR analysis results, these flocculent precipitates and particles should be newly generated Ca-P compounds. The generation of these flocculent precipitates leads to a decrease in the porosity of EC and the disappearance of effective active sites, which ultimately leads to the adsorption saturation of EC materials. The surface of C adsorbent is full of porous structures, and after the adsorption of phosphorus, unknown nano-flower microspheres appear in the pores and attach to them. After the reaction of 750 and 775 in the bead adsorbent, obvious hexagonal crystals (HAP) and flocculent crystals (various Ca-P intermediate compounds in the process of generating HAP) were generated.
[0063] The changes in the surface morphology of the adsorbent after adsorption may be attributed to the reaction between the adsorbent and the solution, which promotes its local dissolution and leads to mechanical wear on the surface of the adsorbent material under stirring conditions.
[0064] The physical properties and main chemical compositions of the powder and adsorbent are shown in Table 1 below. In terms of physical properties, the specific surface area of the EC powder material tends to decrease with the increase of the mass ratio of eggshell to peanut shell. In addition, peanut shell has the highest specific surface area and pore volume, and the biochar fired with the addition of peanut shell will have a higher specific surface area and pore volume. C has the highest specific surface area and the smallest adsorption capacity, while E has the lowest specific surface area and the largest adsorption capacity, which indicates that the pore structure of the adsorbent is not the dominant factor in determining the adsorption capacity of the material. The specific surface area of the bead adsorbent is smaller than that of the powder adsorbent of the corresponding proportion. In terms of chemical composition, as the mass ratio of eggshell to peanut shell in the raw material increases, the proportion of Ca and O elements also increases, but the proportion of C element gradually decreases.
[0065] Table 1
[0066]
[0067] 2. XRD and FTIR analysis before and after biochar adsorption
[0068] From the FTIR and XRD spectra, the following conclusions can be drawn:
[0069] E and EC1∶1 are mainly composed of Ca(OH)2 and CaCO3, and Ca(OH)2 and CaCO3 participate in the phosphorus removal process. After E adsorbs phosphorus, it mainly produces Ca5(PO4)3(OH). After EC1∶1 adsorbs phosphorus, it mainly produces calcium-phosphorus compounds such as Ca3(PO4)2 and Ca2P2O7. KH2PO4 can be observed in the EC1∶1 material after adsorption. The reason for its existence may be due to the physical adsorption of KH2PO4 in the solution by the material, and this physical adsorption may be related to the doping of peanut shells, because peanuts are rich in lignocellulose and have rich pore structure characteristics. There is no obvious change in the characteristic peaks before and after C adsorption, which may be because the components in C hardly react chemically with phosphate.
[0070] EC 1:3-750(b) and EC 1:1-775(b) have CaCO3 and a small amount of Ca(OH)2. After adsorption, other calcium-phosphorus compounds with lower strength appeared. The small amount of Ca(OH)2 and CO3 in EC1:3-750(b) and EC1:1-775(b) 2– CaCO3 is formed, and it is mainly CaCO3 that reacts with phosphorus.
[0071] Example 4
[0072] A recyclable biochar bead adsorbent, the specific preparation method is as follows:
[0073] (1) After egg shell biomass powder (abbreviated as E) and peanut shell biomass powder (abbreviated as C) with a mass ratio of 1:1 and passed through a 100-mesh sieve were fully mixed in deionized water using a magnetic stirrer, sodium alginate was added, and the mixture was fully stirred at about 60° C. for 30 minutes, and naturally cooled to room temperature to obtain a precursor slurry;
[0074] (2) The precursor slurry was dripped into a 5%wt CaCl2 solution to form balls and hardened for 18h; after hardening, the CaCl2 solution on the surface of the carbon beads was cleaned with deionized water; the hydrogel was dried in an oven at 60°C to constant weight; the dried hydrogel beads were calcined in a tubular furnace at 700°C (heating rate 5°C / min) with a nitrogen flow rate of 0.025L / min for 1.5h to finally obtain finished biochar microbeads.
[0075] 0.03 g of the prepared biochar beads were placed in 40 ml of KH2PO4 solution with a pH of 7 and 100 mg / L (in terms of P) and shaken at 180 rpm for 18 h, and the phosphorus concentration after adsorption was measured.
[0076] The test conditions (except for the following conditions which are different from those of the above-mentioned preparation method of this embodiment, the rest are the same) are as follows:
[0077] 1. Effects of CaCl2 on the surface of washed / unwashed carbon beads after hardening and biomass size on the structural stability and adsorption capacity of biochar beads
[0078] Treatment 1 and Treatment 2 were set; Treatment 1: After hardening in step (2), the CaCl2 solution on the surface of the carbon beads was cleaned with deionized water, and different eggshell and peanut shell particle sizes were set (all passed 60 mesh, 80 mesh, and 100 mesh); Treatment 2: After hardening in step (2), the CaCl2 solution on the surface of the carbon beads was not cleaned. The results are shown in Table 1.
[0079] In order to find out the reasons and simplify the experimental steps, it was explored whether the CaCl2 on the surface of washed / unwashed carbon beads after hardening would affect the structural stability and adsorption amount, and whether the biomass size would affect the structural stability and adsorption amount of the prepared biochar beads.
[0080] Table 2 Effects of CaCl2 on the surface of washed / unwashed carbon beads after hardening and biomass size on the structural stability and adsorption capacity of biochar beads
[0081]
[0082] The unwashed carbon beads showed a tendency to expand and powder after one week. A careful observation of the surface of the carbon beads showed that they were absorbing water and damp, which may be caused by the calcium chloride absorbing water on the surface of the carbon beads. The washed carbon beads showed different degrees of expansion after one month, but the degree was less than that of the unwashed ones. In addition, the 100-mesh carbon beads can maintain their original shape well whether they are washed or not.
[0083] The amount of P adsorbed by washed carbon beads increases with decreasing particle size, but the increase is not obvious above 80 mesh; the adsorption capacity of unwashed carbon beads decreases with decreasing particle size.
[0084] In summary, the eggshell modified peanut shell biochar microbeads prepared above are not stable enough except for the carbon beads prepared with biomass that passed through a 100-mesh sieve. In addition, the adsorption capacity of the biochar beads prepared with biomass that passed through a 100-mesh sieve is weak, which may be due to the insufficient degree of pyrolysis of the biochar beads under calcination conditions such as a calcination temperature of 700°C and a calcination time of 1.5h. In order to verify this, the degree of pyrolysis of the carbon beads was increased, and the calcination temperature was raised to 800°C. At the same time, the effects of different calcination times on the structural stability and adsorption properties of the prepared biochar beads were explored.
[0085] 2. Effect of calcination conditions on the structural stability and adsorption capacity of biochar beads
[0086] The calcination temperature was raised to 800°C, and the calcination time was different (1h, 1.5h, 2h). After hardening, the CaCl2 on the surface of the carbon beads was washed with deionized water. The particle sizes of E and C were sieved through a 100-mesh sieve. Except for the above conditions, the preparation method of this embodiment was the same as above. The results are shown in Table 2.
[0087] Table 3 Effect of calcination time on the structural stability and adsorption capacity of biochar beads
[0088]
[0089]
[0090] It can be seen from Table 2 that when the calcination time is 1.5h, as the calcination temperature rises to 800℃, the structure of the carbon beads becomes unstable. Not only do the carbon beads disperse into powder and generate a large amount of flocs during the adsorption process, but the unadsorbed carbon beads can also be easily crushed during shaking. It is considered that the structural instability is caused by the excessive degree of pyrolysis. The morphological changes of the carbon beads in the table with the increase of calcination time verify this. It can be seen from Table 2 that with the increase of calcination time, the phosphorus adsorption capacity increases, the instability of the carbon bead structure increases, and it becomes easy to crush and disperse. In summary, it can be inferred that the longer the calcination time and the higher the calcination temperature, the higher the degree of pyrolysis of the eggshell. The stability of the eggshell structure is closely related to the degree of pyrolysis of the eggshell. If the degree of pyrolysis is too high, the structure is unstable. If the degree of pyrolysis is too low, the adsorption capacity is weak.
[0091] 3. The OLS model was used to verify the above explanation. According to the above conclusions, 38 types of biochar beads were prepared by selecting a suitable range of preparation conditions. The OLS regression model was used to study whether preparation conditions such as calcination temperature, E particle size, C particle size, water washing steps after hardening, EC mass ratio, etc. have a significant effect on the stability of carbon beads and the amount of phosphorus adsorption. In order to better use the OLS regression model to predict the relationship between structural stability and different preparation conditions, the structural stability was approximated as a continuous variable based on the degree of pulverization of carbon beads after phosphorus adsorption observed in the experiment, and it was classified into the following five categories:
[0092] After adsorption, the structure is stable and there is basically no powdering - 1;
[0093] There is a small amount of powderization on the surface of carbon beads after adsorption - 0.75;
[0094] After adsorption, nearly half of the carbon beads are powdered, and the other half remain spherical - 0.5;
[0095] A small amount of carbon beads maintained spherical shape after adsorption—0.25;
[0096] After adsorption, the carbon beads were almost completely dispersed—0;
[0097] The preparation conditions, adsorption capacity and structural stability of the 38 prepared carbon beads are shown in Table 4.
[0098] Table 4 Preparation conditions, adsorption capacity and structural stability of 38 carbon beads
[0099]
[0100]
[0101] Note: Although biochar beads with stable structure can be obtained at a calcination temperature of 700°C, the beads are not durable. After one week, these beads will swell and become loose, and their structural stability will decrease. After adsorption, the beads will disperse.
[0102] From the comprehensive analysis of Table 4, it can be concluded that the structural stability of biochar beads is affected not only by the calcination conditions and biomass particle size, but also by the specific gravity of eggshells.
[0103] Specifically:
[0104] 1) EC 1:1, when calcined at 700℃ for 1.5h, EC is 100 mesh to ensure the stability of the biochar bead structure, and the adsorption capacity is low at this time; 2) However, as the calcination temperature increases to 750℃, the degree of pyrolysis of eggshells in the biochar beads increases, and the EC ratio in the carbon beads must drop to 1:3 to ensure the stability of the carbon bead structure, because the decrease in the specific gravity of E reduces the amount of pyrolyzed eggshells, thereby offsetting the adverse effect of the increase in calcination temperature on structural stability, and ultimately maintaining the spherical structure in a stable state. 3) Even if the EC weight ratio is below 1:3, as long as the particle sizes of E and C are larger than 100 mesh and 60 mesh sieves, respectively, especially when the particle sizes of E and C are relatively large, the prepared carbon beads are quite fluffy, have certain water absorption and moisture characteristics, and are not conducive to long-term storage. Even if the carbon beads are stable when they are just prepared, they will deform after a period of time. Not to mention that the carbon beads maintain a complete spherical shape after adsorption.
[0105] The OLS regression results of the structural stability on the preparation conditions obtained from the data in Table 4 are shown in Table 5.
[0106] Table 5 OLS regression results of carbon bead stability
[0107]
[0108]
[0109] ***p<0.01,**p<0.05,*p<0.1
[0110] The OLS results in Table 5 show that the F statistic indicates that the model is significant with an error probability of 0.0 (p value < 0.01).2 The value is 0.545, which means that the above preparation conditions have an effectiveness of 54.5% in explaining and predicting the structural stability of carbon beads; the structural stability of carbon beads is negatively correlated with calcination temperature, eggshell particle size, peanut shell particle size and the mass ratio of eggshell to peanut shell; for the 0-1 type independent variable water washing after hardening, the average increase in stability of carbon beads washed after hardening is 0.05 more than the average increase in stability of carbon beads not washed after hardening, and its p value is large, and the regression coefficient is not significant. It can be preliminarily judged that the water washing step after hardening has little effect on the structural stability of carbon beads.
[0111] For continuous variables such as calcination temperature, eggshell particle size, peanut shell particle size, and the mass ratio of eggshell to peanut shell, it is generally not rigorous to simply compare the correlation coefficients of the preparation condition variables to derive the degree of influence of each preparation condition on the structural stability of carbon beads. In order to more accurately derive the contribution of the above preparation conditions to the structural stability of carbon beads, it is necessary to consider the influence of the value range of the independent variable and the dependent variable on the final biochar structural stability. The calculation method is: for every increase of one standard deviation in the independent variable, the dependent variable will increase by [β*standard deviation value], and the percentage of the increase in the average value of the dependent variable is calculated.
[0112] The results are as follows: for calcination temperature, for every standard deviation increase, the structural stability of carbon beads will decrease by 0.202, and the decrease accounts for 48.2% of the mean value of the dependent variable; for eggshell particle size, for every standard deviation increase, the structural stability of carbon beads will decrease by 0.118, and the decrease accounts for 28.1% of the mean value of the dependent variable; for peanut shell temperature, for every standard deviation increase, the structural stability of carbon beads will decrease by 0.112, and the decrease accounts for 26.6% of the mean value of the dependent variable; for the mass ratio of eggshell to peanut shell, for every standard deviation increase, the structural stability of carbon beads will decrease by 0.186, and the decrease accounts for 44.3% of the mean value of the dependent variable.
[0113] Within the range of preparation conditions, the influence of the above continuous variables on the structural stability of carbon beads is ranked as follows: calcination temperature > mass ratio of eggshell to peanut shell > eggshell particle size > peanut shell particle size. Even the peanut shell particle size, which has the lowest influence, has a significant regression coefficient at the level of p<0.05, indicating that biomass particle size plays an important role in the structural stability of carbon beads.
[0114] The OLS regression results of the adsorption amount obtained from the data in Table 4 on the preparation conditions are shown in Table 6:
[0115] Table 6 OLS regression results of carbon bead phosphorus absorption capacity
[0116]
[0117] ***p<.01,**p<.05,*p<.1
[0118] The OLS results in Table 6 show that the F statistic indicates that the model is significant with an error probability of 0.0 (p value < 0.01). 2 The value is 0.534, which means that the above preparation conditions have 53.4% effectiveness in explaining and predicting the structural stability of carbon beads; the phosphorus adsorption of carbon beads is negatively correlated with the peanut shell particle size, and positively correlated with the calcination temperature, eggshell particle size and EC mass ratio; for the 0-1 type independent variable of the water washing step after hardening, the average increase in stability of the carbon beads washed after hardening is -11.5 compared with the average increase in stability of the carbon beads without water washing after hardening, and its p value is large, and the regression coefficient is not significant. It can be judged that the water washing step after hardening has little effect on the phosphorus absorption of carbon beads. In addition, for the continuous variable preparation condition variables eggshell particle size and peanut shell particle size, its p value is too large, and the regression coefficient is not significant. It can be said that compared with the influence of changes in other variables with significant regression coefficients, the change of biomass particle size within 0.15~0.4mm has very little effect on the phosphorus adsorption of biochar beads. Further analysis of other continuous variables will be carried out later.
[0119] As shown in Table 6, a comparative analysis of the influence of preparation conditions with significant regression coefficients on the adsorption amount was conducted, and the results are as follows: for calcination temperature, for every increase of one standard deviation, the phosphorus adsorption amount of carbon beads will increase by 24.3, and the increase accounts for 27.5% of the average value of the dependent variable; for EC mass ratio, for every increase of one standard deviation, the phosphorus adsorption amount of carbon beads will increase by 22.4, and the decrease accounts for 25.4% of the average value of the dependent variable.
[0120] Within the above preparation conditions, the order of influence of continuous variables on the phosphorus adsorption of carbon beads is: calcination temperature > mass ratio of eggshell to peanut shell.
[0121] Combining the analysis results of Table 5 and Table 6, it can be concluded that: within the preparation conditions, calcination temperature and EC mass ratio have the greatest impact on the phosphorus adsorption capacity and structural stability of carbon beads. The difference is that the structural stability of carbon beads is negatively correlated with the two variables, while the phosphorus adsorption capacity of carbon beads is positively correlated with the two variables. This to a certain extent shows that the high phosphorus adsorption performance of carbon beads is achieved at the cost of a decrease in the structural stability of carbon beads; the biomass particle size has a greater impact on the structural stability of carbon beads, and the washing process after the gel beads are hardened will reduce the adsorption capacity of carbon beads.
Claims
1. A method for preparing a recyclable biochar bead adsorbent, characterized in that: The following steps are involved: (1) Eggshell biomass powder and peanut shell biomass powder were mixed in water in proportion, sodium alginate was added, and the mixture was heated to dissolve, and then naturally cooled to room temperature to obtain a precursor slurry; the heating and dissolving temperature was 60°C, and the stirring time was 30 min; The mass ratio of the egg shell biomass powder to the peanut shell biomass powder is 1:3; the particle size of the egg shell biomass powder is 0.15 mm; the particle size of the peanut shell biomass powder is 0.15 mm; The mass percentage of egg shell biomass powder and peanut shell biomass powder in water is 4-6wt%; the mass percentage of sodium alginate in the precursor slurry is 1.5-3wt%; (2) The precursor slurry of step (1) is dropped into a CaCl2 aqueous solution to harden it into balls. After the precursor slurry is dropped into the CaCl2 aqueous solution, the mass percentage of CaCl2 is 5wt% and the hardening time is 18 h. The hardened hydrogel balls are first washed with deionized water and then dried to constant weight. They are then calcined at 775°C for 1.5 h in a nitrogen atmosphere to obtain a biochar bead adsorbent. The heating rate during the calcination process is 5°C / min.
2. Application of the biochar bead adsorbent prepared by the preparation method as claimed in claim 1 in adsorbing phosphate in water.
Citation Information
Patent Citations
Eggshell straw biochar composite microsphere phosphorus removal adsorbent with high adsorption performance, and preparation method and application thereof
CN111701568A